Peranan Badan Usaha Milik Desa (Bumdes) Dalam Peningkatan Perekonomian Masyarakat Di Desa Tanah Merah (Studi Kasus Pada Bumdes Pabrik Tahu Desa Tanah Merah Kecamatan Galang Kabupaten Deli Serdang) - Rahmi Syahriza; Jihan Atiqah Pane; Farah Indah Azhari; Asyaadatun Nazila Selayan; Meliyani Meliyani; Mutiara Azhari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine, describe, and analyze the role of Village Owned Enterprises (BUMDes) in supporting village economic independence, as well as to determine the obstacles and success of BUMDes. The improvement of the rural economy is carried out by the village government through various programs with the aim of community welfare. BUMDes management is fully implemented by village communities who take on roles, namely from the village, by the village, and for the village. In analyzing research data using qualitative descriptive methods, only describe the results of interview questions in the field. The results of the study indicate that BUMDes which has formed an entrepreneurial business entity in the form of a tofu factory has an important role in supporting village economic independence because the village economy is able to become the main center for improving village development progress. Some of the obstacles that occur in BUMDes due to the lack of human resources and the large rental costs can now be overcome by the increasingly significant profits of BUMDes.